Pengembangan Rencana Pelaksanaan Pembelajaran dan Bahan Ajar dalam Kompetensi Dasar Perdagangan Internasional Dengan Menggunakan Media Berbasis Android - Hijratul Husna; Yulhendri Yulhendri (Jurnal Ecogen, 2022)
COVID-19 has had an impact on health and education crises. One of the perceived impacts is in learning economics on international trade material which contains a lot of material which makes learning boring. Efforts are made to carry out interesting learning by utilizing lesson plans and teaching materials using android-based learning media. The research method is Research & Development, with the ADDIE model, this research is limited to the Development stage. The research objective is to analyze the level of validity and practicality of lesson plans and teaching materials using Android-based media. The research instrument in the form of a questionnaire given to 10 validator lecturers consisting of 3 Lesson plan experts with an average score of 90.36%, 3 material experts with an average score of 86.86%, 1 evaluation expert lecturer with an average score 97.5% and 3 media experts with an average score of 95.29%, from the overall assessment of the validators categorized as very valid. Practicality tests were conducted on 3 economics teachers with an average score of 90.24% including the very valid category and students with an average score of 86.08% including the very valid category. Keywords : lesson plans, teaching materials, learning media, android international trade, ADDIE